Informal intellectual collaboration with central colleagues - Co-Pierre Georg; Daniel C. Opolot; Michael E. Rose (Kiel Institute for the World Economy (IfW), 2017)
When preparing a research article, academics engage in informal intellectual collaboration by asking their colleagues for feedback. This collaboration gives rise to a social network between academics. We study whether informal intellectual collaboration with an academic who is more central in this social network results in a research article having higher scientific impact. To address the well-known reflection problem in estimating network effects, we use the assignment of discussants at NBER summer institutes as a quasi-natural experiment. We show that manuscripts discussed by a discussant with a 10% higher than average Bonacich centrality rank results in 1.4% more citations and a 5% higher probability that an article is published in a top journal. To illustrate our results, we develop a structural model in which a positive externality from intellectual collaboration implies that collaborating with a more central colleague results in larger scientific impact of the research article.
Keywords: A14; D83; G00; O33; 330; informal intellectual collaboration; social network; scientific impact; centrality